KARAKTERISASI AKSESI KACANG PANJANG (Vigna unguiculata subsp. sesquipedalis) LOKAL - Nafila Alifia Azka; Rahmi Sri Sayekti (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2020)
Indonesia is the center of yardlong bean cultivation, so that it has a wide genetic diversity. The Vegetable Genebank of Universitas Gadjah Mada has a large collection of yardlong bean germplasm. Therefore, it is necessary to characterize the germplasm collection to identify the specific characters of each accession. Morphological characterization of yardlong bean was carried out based on quantitative and qualitative traits. The yardlong bean accessions that were being observed in this research were FB-KP 277, FB-KP 431, FB-KP 688, FB-KP 689, FB-KP 690, and FB-KP 728.The result showed that FB-KP 728 had the highest yield potential. Meanwhile, the yardlong bean accession with the lowest yield potential was FB-KP 277. FB-KP 277 was the only yardlong bean accession that had the specific characteristics, they were twining growth type, pale green leaf color, ovate leaf shape, and brown-cream seed color.